68Ga-PSMA-11 PET/CT combining ADC value of MRI in the diagnosis of naive prostate cancer: Perspective of radiologist. Issue 36 (4th September 2020) - Wang, Liwei; Yu, Fei; Yang, Lulu; Zang, Shiming; Xue, Hailin; Yin, Xindao; Guo, Hongqian; Sun, Hongbin; Wang, Feng
Abstract : Abstract: 68 Ga-PSMA-11 positron emission computed tomography /computed tomography (PET/CT) is more sensitive than magnetic resonance imaging (MRI) in detecting prostate cancer (PCa). We evaluated the value of 68 Ga-PSMA-11 PET/CT with MRI in treatment-naive PCa. This retrospective study was approved by the hospital ethics committee. The MRI and 68 Ga-PSMA-11 PET/CT imaging data of 63 cases of highly suspected PCa were enrolled in this study. The SUVmax and apparent diffusion coefficient (ADC), and their ratio, were assessed as diagnostic markers to distinguish PCa from benign disease. There were 107 prostate lesions detected in 63 cases. Forty cases with 64 malignant primary lesions were confirmed PCa, whereas 23 cases had 43 benign lesions. PSMA-avid lesions correlated with hypointense signal on ADC maps and hyperintense signal on diffusion-weighted imaging. The ADC of PCa was lower than that of benign lesions, and SUVmax and SUVmax /ADC of PCa was higher than that of benign lesions ( P  < .01). ADC had significant negative correlation with Gleason score (GS) and SUVmax, SUVmax, and SUVmax /ADC positively correlated with GS. From ROC analysis, we established cutoff values of ADC, SUVmax, and SUVmax /ADC at 1.02 × 10 −3 mm 2 /s, 11.72, and 12.35, respectively, to differentiate PCa from benign lesions. The sensitivity, specificity, and AUC were 90.6%, 58.1%, and 0.816 for ADC, 67.2%, 97.7%, and 0.905 for SUVmax, and 81.2%, 88.4%, and 0.929 for SUVmax /ADC, respectively. 68 Ga-PSMA-11 PET/CT combined with MRI offers higher diagnostic efficacy in the detection of PCa than either modality alone.